KEEFEKTIFAN KETEBALAN ARANG TEMPURUNG KELAPA DAN PASIR DALAM PENURUNAN KESADAHAN DI DUSUN GAMPENG RT 01, TRIWIDADI, PAJANGAN, BANTUL - Rois, Ibnu; Amalia Hapsari, Citra; Santjoko, Herman (Jurnal Sanitasi Profesional Indonesia, 2022)
Water is a basic need for human life. The problem faced is the high hardness of the well water, the water hardness level is a very hard level. If this consumed continuously, it will cause health problems, namely kidney function. This study aims to determine the level of water hardness reduction in dug wells using variations in the thickness of coconut shell activated charcoal, namely 40, 60, and 80 cm through a 90 cm sand filter. The type of research carried ous is a non-random experimental design or also Non-randomized pretest-posttest control group design. The results showed a decrease in the level of hardness after passing coconut shell activated charcoal at a thickness of 40 cm and sand filter of 90 cm by 169 mg/L or 37.97%, coconut shell activated charcoal at a thickness of 60 cm and sand filter of 90 cm by 230.33 mg/L or 51.75%, and coconut shell activated charcoal at a thickness of 80 cm and sand filter of 90 cm by 297.8 mg/L or 66.91%. the results on One Way Anova test show the sig. 0,002 < 0,05, so it assumed that the thickness variation of coconut shell activated charcoal in the dug well water filtration process affects the decrease in hardness. Based on the results of the study, the most effective filtering results were 80 cm thickness of 297.8 mg/L or 66.91%.